A Study on Utilization Potential of Microbial Biopolymer treated Wastes in Civil Engineering - Bonal, Niteesh Singh (IIT(BHU) Varanasi, 2022)
Abstract is available in the content.
Keywords: A Study on Utilization; Potential of Microbial Biopolymer; treated Wastes in Civil Engineering